Lets write each part, the total will be x:
(1/10)x = Europe
3200 = Asia
x - <span>(1/10)x - 3200 = Africa
Europe + Asia = </span><span>(1/10)x + 3200 = x/10 + 3200
= (320x + 1)/3200
that would be expressed as a fraction, and depends on the total of coins, x</span>
Answer:
Part 1) The algebraic expression is equal to
or ![1.10n-1.10](https://tex.z-dn.net/?f=1.10n-1.10)
Part 2) The algebraic expression is equal to ![\frac{1.10}{n}](https://tex.z-dn.net/?f=%5Cfrac%7B1.10%7D%7Bn%7D)
Step-by-step explanation:
Part 1) we have (n-1) increased by 110%
110%=110/100=1.10
so
The algebraic expression of (n-1) increased by 110% is equal to multiply 1.10 by (n-1)
![1.10(n-1)](https://tex.z-dn.net/?f=1.10%28n-1%29)
Distributed
![1.10n-1.10](https://tex.z-dn.net/?f=1.10n-1.10)
Part 2) we have n^(-1) increased by 110%
110%=110/100=1.10
so
The algebraic expression of n^(-1) increased by 110% is equal to multiply 1.10 by n^(-1)
Remember that
![n^{-1}=\frac{1}{n}](https://tex.z-dn.net/?f=n%5E%7B-1%7D%3D%5Cfrac%7B1%7D%7Bn%7D)
so
![1.10(n^{-1})=1.10\frac{1}{n}=\frac{1.10}{n}](https://tex.z-dn.net/?f=1.10%28n%5E%7B-1%7D%29%3D1.10%5Cfrac%7B1%7D%7Bn%7D%3D%5Cfrac%7B1.10%7D%7Bn%7D)
Answer:
The volume of the right rectangular prism is 5400 cubic centimeter.
Step-by-step explanation:
Given : The length of the prism is 45 cm, the width is 12 cm, and the height is 10 cm.
To find : The volume of a right rectangular prism ?
Solution :
The formula used is ![V=l\times w\times h](https://tex.z-dn.net/?f=V%3Dl%5Ctimes%20w%5Ctimes%20h)
Where, l is the length of the prism l=45 cm
w is the width of the prism w=12 cm
h is the height of the prism h=10 cm
Substitute the value in the formula,
![V=45\times 12\times 10](https://tex.z-dn.net/?f=V%3D45%5Ctimes%2012%5Ctimes%2010)
![V=5400\ cm^3](https://tex.z-dn.net/?f=V%3D5400%5C%20cm%5E3)
Therefore, The volume of the right rectangular prism is 5400 cubic centimeter.
Answer:
question no 1:slope=5
Step-by-step explanation:
let(x=5andy=8)(a=7andb=18)
now
slope=(b-y)/(a-x)=(18-8)/(7-5)=5
f(x) = 1 - ²/ₓ₃
y = 1 - ²/ₓ₃
y = 1 - ²/ₓ₃
y - 1 = ⁻²/ₓ₃
x - 1 = -2/y³
y³(x - 1) = -2
y³ = ⁻²/ₓ₋₁
y = ∛⁻²/ₓ₋₁
y = -∛(2x² - 4x + 2)/x - 1
f⁻¹(x) = -∛(2x² - 4x + 2)/x - 1